2003
DOI: 10.1038/sj.sc.3101492
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effect of hippotherapy on spasticity in patients with spinal cord injury

Abstract: Study design: Assessment of spasticity before and after hippotherapy treatment. Objective: To evaluate the short-term effect of hippotherapy on spasticity of spinal cord injured patients (SCIs). Setting: Swiss Paraplegic Centre, Nottwil. Methods: 32 patients with spinal cord injury with various degrees of spasticity had repeated sessions (mean 11) of Hippotherapy-K s . Spasticity of the lower extremities was scored according to the Ashworth Scale. Results: In primary rehabilitation patients Ashworth values aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 7 publications
0
30
0
8
Order By: Relevance
“…Otros estudios demuestra los efectos percibidos generales de la hipoterapia entre ellos la regulación del tono muscular (16,17) aspecto que es ratificado con los resultados hallados.…”
Section: Discussionunclassified
“…Otros estudios demuestra los efectos percibidos generales de la hipoterapia entre ellos la regulación del tono muscular (16,17) aspecto que es ratificado con los resultados hallados.…”
Section: Discussionunclassified
“…This can be evidenced on the subjects who participated in the experimental group, obtaining a significant improvement in motor impairment, while the control group did not (p-value=0.004). Tarnow, apud Lechner et al 18 , found in his study that children and adolescents with spastic quadriplegia showed a clear improvement in trunk flexibility and functional capacity after treatment with the horseback riding therapy.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 En un estudio realizado en 12 sujetos con lesión medular (clasificación A y B, según la Asociación Americana de Lesión Medular ASIA), luego de 15 sesiones de 25 minutos durante cuatro semanas, encontraron una disminución estadísticamente significante p <0,04, aunque estos cambios fueron de corta duración. [56][57][58][59][60] d. Efectos cognitivos, sociales y emocionales Montar a caballo supone una serie de emociones, interacciones y procesos cognitivos que parten de la motivación del jinete o la amazona; desde lo cognitivo se pueden citar algunos beneficios tales como, la focalización de la atención, estructuración de actividades de forma secuencial, seguimiento y acatamiento de órdenes, desensibilización a ciertos miedos o temores, imaginación, creatividad, respuestas lógicas, autocontrol, toma de decisiones, resolución de problemas o simplemente el placer y el alcance de un logro no antes contemplado por el paciente que reposa sobre el lomo de un caballo sea cual sea su posibilidad o funcionalidad. 61 Desde el aspecto social la hipoterapia abre espacios enriquecedores de experiencias gratificantes que son subjetivas de cada jinete/amazona, las cuales van desde la respuesta de interacción recíproca, la empatía, la inclusión, la responsabilidad, la posibilidad de comunicación, la aceptación en un rol y la participación en las actividades que permiten que el jinete/amazona se sienta querido, comprendido y útil a través de su desempeño independiente o dependiente.…”
Section: Tono Muscularunclassified